1996
DOI: 10.1128/jb.178.11.3252-3259.1996
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic biosynthesis of enterobactin Escherichia coli: regulation of entC gene expression and evidence against its involvement in menaquinone (vitamin K2) biosynthesis

Abstract: In Escherichia coli, isochorismate is a common precursor for the biosynthesis of the siderophore enterobactin and menaquinone (vitamin K 2 ). Isochorismate is formed by the shikimate pathway from chorismate by the enzyme isochorismate synthase encoded by the entC gene. Since enterobactin is involved in the aerobic assimilation of iron, and menaquinone is involved in anaerobic electron transport, we investigated the regulation of entC by iron and oxygen. An operon fusion between entC with its associated regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 33 publications
4
25
0
Order By: Relevance
“…Consistent with this observation is the recent demonstration that enterobactin is synthesized both aerobically and anaerobically (6). Since menaquinone is synthesized both aerobically and anaerobically (at a higher level) and functions anaerobically, the reaction carried out by MenF will be similar in the utilization of water as the source of the hydroxyl group.…”
supporting
confidence: 69%
See 1 more Smart Citation
“…Consistent with this observation is the recent demonstration that enterobactin is synthesized both aerobically and anaerobically (6). Since menaquinone is synthesized both aerobically and anaerobically (at a higher level) and functions anaerobically, the reaction carried out by MenF will be similar in the utilization of water as the source of the hydroxyl group.…”
supporting
confidence: 69%
“…The various enzymes involved in the menaquinone biosynthetic pathway are present at extremely low levels, and among these, the menF-encoded isochorismate synthase is the least active. In the entC mutant (which lacks the EntC isochorismate synthase), the MenF activity was reported to be 0.6 nmol h Ϫ1 mg of protein Ϫ1 (6). The strain in which the protein was overexpressed produced 45 nmol of isochorismate min Ϫ1 mg of protein…”
Section: Discussionmentioning
confidence: 99%
“…The mutant was able to grow at the same rate as the parent, even in the presence of high concentrations of iron. Further, the mutant produced as much MK as the parent (91,93,104). These results provided clear evidence for the presence of an alternate isochorismate synthase specifically involved in MK biosynthesis.…”
Section: Formation Of Isochorismate (Compound IV -------> V)supporting
confidence: 53%
“…To study the regulation of the entC gene, an entC-lacZ operon fusion was constructed and the expression of β-galactosidase monitored under various conditions. It was found that the β-galactosidase was fully derepressed at low concentration of iron and repressed at high iron concentrations under both aerobic and anaerobic growth conditions (91,93).…”
Section: Formation Of Isochorismate (Compound IV -------> V)mentioning
confidence: 99%
“…To construct ⌽(arcB -malF [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] arcB ), PCR was performed with pIBW as a template and BPH-N and BMF-22 as primers. The purified PCR product and BMF-35 were used as primers for the second PCR with pDHB32 (6) as a template.…”
Section: Fig 3 Effects Of Substituting Segments Of Arcb Withmentioning
confidence: 99%